A LDH-based composite phase change material with light-to-heat conversion performance and a preparation method thereof
By synthesizing LDH-based composite phase change materials with uniformly distributed metal nanoparticles in the composite phase change material using ZIF-67 template, the problem of nanoparticle agglomeration is solved and efficient photothermal conversion and storage performance is achieved.
Patent Information
- Application Number
- CN202211664227.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-12-22
AI Technical Summary
Existing composite phase change materials are prone to agglomeration under the action of van der Waals forces and chemical bonds between nanoparticles, affecting their photothermal conversion performance.
ZIF-67 is used as a template to synthesize layered bimetallic hydroxide (LDH) with uniformly distributed metal elements by chemical etching, and reduce it in situ under a reducing atmosphere to obtain a phase change carrier of uniformly dispersed metal nanoparticles, and then compound with the phase change core material to form an LDH-based composite phase change material with photothermal conversion performance.
The uniform distribution of nanoparticles is achieved, the thermal conductivity and photothermal conversion performance of composite phase change materials are improved, and the heat can be quickly stored and released, and the preparation process is simple and economical.
Smart Images

Figure CN115820216B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of composite phase change materials, and more specifically, to an LDH-based composite phase change material with light-to-heat conversion performance and a preparation method thereof. Background Art
[0002] With the rapid development of industrialization, while mineral energy (such as coal, natural gas, oil, etc.) is facing the crisis of depletion, environmental pollution problems are becoming more and more serious. Phase change materials have the advantages of high energy storage density and low temperature domain changes, and have attracted widespread attention in improving energy efficiency and developing new energy sources. In particular, new composite phase change materials with energy conversion functions can effectively realize energy conversion and storage. Among various energy sources, solar energy is the most potential renewable clean energy, so photothermal conversion composite phase change materials are the most frequently studied composite phase change materials in energy conversion. Combining nanoparticles with local surface plasmon resonance effect with phase change materials to prepare composite phase change materials, and using composite phase change materials to store and release thermal energy is an effective way to solve the problem of spatial and temporal mismatch between thermal energy supply and demand, and is one of the important means to improve energy efficiency.
[0003] Due to the inherent weak photon capture ability, traditional phase change materials cannot effectively capture light energy and achieve photothermal conversion. Therefore, the method of introducing nanoparticles with light capture ability into phase change materials to achieve photothermal conversion has attracted widespread attention. 2 O 3 A method for preparing a composite phase change material with light-heat conversion function by combining nanoparticles with phase change materials. Patent CN106010458A discloses a Cu-CuO 2 / CNT as a shell layer, coated with paraffin to form a microcapsule for photothermal conversion composite phase change energy storage material and its preparation method. However, the above composite phase change materials are directly added to the carrier material or synthesized in the solution, but due to the strong van der Waals force and chemical bonds between the nanoparticles, agglomeration will inevitably occur when directly added or directly synthesized in the solution, which will affect the photothermal conversion performance of the nanocomposite material. In order to obtain excellent performance of photothermal conversion nanocomposite materials, avoiding the agglomeration of nanoparticles is an indispensable prerequisite. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present application provides an LDH-based composite phase change material with photothermal conversion performance and a preparation method thereof. The method uses ZIF-67 as a template, chemically etches it to synthesize a layered double hydroxide (LDH) with uniform distribution of metal elements, and in-situ reduces it under a reducing atmosphere to obtain a phase change carrier with uniformly dispersed metal nanoparticles; and then composites it with a phase change core material to form an LDH-based composite phase change material with photothermal conversion performance. The present application cleverly and effectively solves the problem of easy agglomeration of nanoparticles, and realizes the uniform distribution of nanoparticles with local surface plasmon resonance effect in the phase change carrier. The present application realizes efficient and rapid photothermal energy conversion and storage, has a simple preparation process, a variety of phase change carriers and phase change core materials, and has good economy.
[0005] In order to achieve the above objectives, in a first aspect, the present application provides a method for preparing an LDH-based composite phase change material with light-to-heat conversion performance, comprising the following steps:
[0006] Step 1: Using ZIF-67 as a template, chemically etching it with different metal salts to obtain LDH with uniform distribution of different metal elements;
[0007] Step 2: calcining in a reducing atmosphere to reduce the metal elements in the LDH with uniform metal element distribution to metal nanoparticles in situ, thereby obtaining a phase change carrier with uniformly dispersed metal nanoparticles;
[0008] Step 3: Compounding the phase change carrier and the phase change core material.
[0009] Furthermore, the specific method of step 1 is:
[0010] Step 1.1: Co(NO 3 ) 2 and 2-methylimidazole (2-MIM) as precursors, and allowed to stand in methanol at room temperature for 12 to 24 hours to synthesize dodecahedral ZIF-67;
[0011] Step 1.2: Dissolve ZIF-67 in ethanol solution (concentration of 2.5-14 g / L), and dissolve different types of metal salts in deionized water (concentration of 1.5-30 g / L), and perform ultrasonic treatment for 5-15 minutes respectively;
[0012] Step 1.3: The two solutions in step 1.2 are then mixed and reacted at 60-80° C. for 15 min to 24 h to obtain LDH with uniform distribution of different metal elements.
[0013] Furthermore, the metal salt includes one or more of iron salt, molybdenum salt and nickel salt; the LDH with uniform distribution of different metal elements includes one or more of Mo-Co LDH, Ni-Co LDH and Fe-Co LDH.
[0014] Furthermore, the specific method of step 2 is: placing the LDH with uniform distribution of different metal elements obtained in step 1 in a crucible, heating it at 300-450°C for 2-3h at a heating rate of 1-2°C / min under a reducing atmosphere, and cooling it to room temperature to obtain a phase change carrier with uniformly dispersed metal nanoparticles.
[0015] Preferably, the reducing atmosphere is a mixed atmosphere of 5% hydrogen and 95% argon.
[0016] Furthermore, the specific method of step 3 is: vacuum the phase change carrier prepared in step 2 at 80°C to 120°C for 4 hours, then disperse it in a solution containing the phase change core material, heat it to 25 to 100°C, stir it for 1 to 24 hours, and then filter it, and finally place it in a 50 to 120°C oven to dry for 2 to 24 hours.
[0017] Furthermore, the phase change core material includes a mixture of polyols, fatty acids and hydrocarbons.
[0018] Preferably, the polyol includes one or more of polyethylene glycol 1000-20000, pentaerythritol, and neopentyl glycol; the fatty acid includes one or more of stearic acid, myristic acid, palmitic acid, capric acid, lauric acid, pentadecanoic acid, and sebacic acid; and the hydrocarbon mixture is paraffin.
[0019] Furthermore, the solution containing the phase change core material is an aqueous solution, an alcohol solution or a n-hexane solution; the concentration of the solution containing the phase change core material is 10-15 g / L, and the loading amount of the composite phase change material is 50-80%.
[0020] In a second aspect, the present invention provides an LDH-based composite phase change material with light-to-heat conversion performance, which is prepared using the above-mentioned preparation method.
[0021] The technical solution provided by this application has at least the following beneficial effects compared with the prior art:
[0022] 1) The preparation method of the LDH-based composite phase change material with light-heat conversion performance provided in the present application is to use ZIF-67 as a template, chemically etch it to synthesize LDH with uniform distribution of metal elements, and in-situ reduce it under a reducing atmosphere to obtain a phase change carrier with uniformly dispersed metal nanoparticles; and then compound it with a phase change core material to form an LDH-based composite phase change material with light-heat conversion performance. The present application cleverly solves the problem that metal nanoparticles in the phase change carrier are easy to agglomerate, and realizes the uniform distribution of nanoparticles with local surface plasmon resonance effect in the phase change carrier.
[0023] 2) The LDH-based composite phase change material with light-to-heat conversion performance provided by the present application has uniformly distributed metal nanoparticles that provide a channel for heat transfer, shorten the heat transfer path, and can effectively improve the thermal conductivity of the composite phase change material, thereby achieving rapid storage and release of heat;
[0024] 3) The LDH and phase change core materials used in the preparation method of the present application are diverse in selection and have good economic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM photo of the phase change carrier obtained in Example 1 of the present invention;
[0026] Figure 2 This is a DSC curve of the LDH-based composite phase change material with light-to-heat conversion performance obtained in Example 1 of the present invention;
[0027] Figure 3 The light-to-heat conversion curves of the composite phase change materials prepared in Example 1 and Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to understand the present application more clearly, the present application is further described in detail below in conjunction with examples and drawings. However, it should be understood that the following examples are only preferred implementation methods of the present application, and the scope of protection required by the present application shall be based on the scope defined in the claims.
[0029] <Example>
[0030] Example 1
[0031] A method for preparing an LDH-based composite phase change material with light-to-heat conversion performance comprises the following steps:
[0032] Step 1: Co(NO 3 ) 2and 2-methylimidazole (2-MIM) as precursors, and allowed to stand in methanol at room temperature for 24 hours to synthesize dodecahedral ZIF-67; 0.2 g of ZIF-67 was dissolved in 80 mL of ethanol solution to obtain solution A, and 0.06 g of (NH 4 ) 6 Mo 7 O 4 The solution was dissolved in 20 mL of deionized water to obtain solution B. After ultrasonic treatment for 5 min, solution B was poured into solution A and then ultrasonicated for 1 min to mix evenly. The solution was then poured into a round-bottom flask and reacted at 85 ° C for 15 min under condensation reflux conditions. After cooling to room temperature, it was washed by centrifugation with ethanol and deionized water several times and dried at 60 ° C for 24 h to obtain LDH with uniform distribution of different metal elements (Mo-Co LDH).
[0033] Step 2: Take 0.150 g of Mo-Co LDH prepared in step 1 and put it into a crucible. 2 The temperature was raised to 450°C at a rate of 2°C / min in a mixed gas of 95% Ar and kept at 450°C for 2h to obtain a phase change carrier with uniformly dispersed Co nanoparticles. The SEM photo of the phase change carrier is shown in Figure 1 As shown;
[0034] Step 3: Take 0.150 g of the phase change carrier prepared in step 2 and evacuate it at 120 ° C for 4 hours to remove the small molecules in the pores; then disperse it in 10 mL of n-hexane solution containing 0.35 g of paraffin (PW), stir it at 60 ° C for 2 hours, place the mixture in an 80 ° C drying oven, keep it warm for 24 hours, and collect the LDH-based composite phase change material with photothermal conversion performance.
[0035] Example 2
[0036] A method for preparing an LDH-based composite phase change material with light-to-heat conversion performance comprises the following steps:
[0037] Step 1: Co(NO 3 ) 2 and 2-methylimidazole (2-MIM) as precursors, and allowed to stand in methanol at room temperature for 24 hours to synthesize dodecahedral ZIF-67; 0.35 g of ZIF-67 was dissolved in 80 mL of ethanol solution to obtain solution A, and 0.15 g of Ni(NO 3 ) 2Dissolve in 5 mL of deionized water to obtain solution B, and then pour solution B into solution A and sonicate for 1 min to mix them evenly. Then pour the solution into a round-bottom flask, react at 80 ° C for 6 h, cool to room temperature, centrifuge and wash with ethanol and deionized water several times, and dry at 60 ° C for 24 h to obtain LDH (Ni-CoLDH) with uniform distribution of different metal elements;
[0038] Step 2: Take 0.150 g of Ni-Co LDH prepared in step 1 and put it into a crucible. 2 The temperature was raised to 300°C at a rate of 2°C / min in a mixed gas of 95% Ar and kept at 300°C for 2h to obtain a phase change carrier with uniformly dispersed Ni and Co nanoparticles;
[0039] Step 3, take 0.150g of the phase change carrier prepared in step 2 and evacuate it at 120℃ for 4h to remove the small molecules in the pores; then disperse it in 10mL of anhydrous ethanol solution containing 0.35g PEG10000, stir it at 60℃ for 2h, place the mixture in an 80℃ drying oven, keep it warm for 24h, and collect the LDH-based composite phase change material with photothermal conversion performance.
[0040] Example 3
[0041] A method for preparing an LDH-based composite phase change material with light-to-heat conversion performance comprises the following steps:
[0042] Step 1: Co(NO 3 ) 2 and 2-methylimidazole (2-MIM) as precursors, and allowed to stand in methanol at room temperature for 24 hours to synthesize dodecahedral ZIF-67; 0.2 g of ZIF-67 was dissolved in 15 mL of ethanol solution to obtain solution A, and 0.15 g of Fe(NO 3 ) 3 The solution was dissolved in 80 mL of deionized water to obtain solution B. After ultrasonication for 5 min, solution B was poured into solution A and ultrasonicated for 1 min to mix evenly. The solution was then poured into a round-bottom flask and heated with NaOH and NaCO 3 The pH was adjusted to 10 and stirred for 30 min, followed by reaction at 65 °C for 24 h. After cooling to room temperature, the mixture was centrifuged and washed several times with ethanol and deionized water, and dried at 70 °C for 12 h to obtain LDH (Fe-Co LDH) with uniform distribution of different metal elements.
[0043] Step 2: Take 0.150 g of Fe-Co LDH prepared in step 1 and put it into a crucible. 2The temperature was raised to 350°C at a rate of 2°C / min in a mixed gas of 2% Ar and 95% Ar, and kept at 350°C for 3h to obtain a phase change carrier with uniformly dispersed Fe and Co nanoparticles.
[0044] Step 3: Take 0.150 g of the phase change carrier prepared in step 2 and evacuate it at 120 ° C for 4 hours to remove the small molecules in the pores; then disperse it in 10 mL of anhydrous ethanol solution containing 0.15 g PEG10000, stir it at 60 ° C for 2 hours, place the mixture in an 80 ° C drying oven, keep it warm for 12 hours, and collect the LDH-based composite phase change material with photothermal conversion performance.
[0045] Comparative Example 1
[0046] Step 1: Co(NO 3 ) 2 and 2-methylimidazole (2-MIM) as precursors, and allowed to stand in methanol at room temperature for 24 hours to synthesize dodecahedral ZIF-67; 0.2 g of ZIF-67 was dissolved in 80 mL of ethanol solution to obtain solution A, and 0.06 g of (NH 4 ) 6 Mo 7 O 4 The solution was dissolved in 20 mL of deionized water to obtain solution B. After ultrasonic treatment for 5 min, solution B was poured into solution A and then ultrasonicated for 1 min to mix evenly. The solution was then poured into a round-bottom flask and reacted at 85 ° C for 15 min under condensation reflux conditions. After cooling to room temperature, it was washed by centrifugation with ethanol and deionized water several times and dried at 60 ° C for 24 h to obtain LDH with uniform distribution of different metal elements (Mo-Co LDH).
[0047] Step 2: Take 0.150 g of the Mo-Co LDH prepared in step 1 and put it into a beaker, and dissolve it in 30 ml of deionized water; take 0.053 g of Co element and add it to the aqueous solution of Mo-Co LDH, stir it at room temperature for 3 hours, wash it with deionized water by centrifugation several times, and dry it at 60°C for 24 hours to obtain a phase change carrier of nanoparticles and LDH physically mixed.
[0048] Step 3: Take 0.150 g of the phase change carrier prepared in step 2 and evacuate it at 120°C for 4 hours to remove the small molecules in the pores; then disperse it in 10 mL of n-hexane solution containing 0.35 g of paraffin (PW), stir it at 60°C for 2 hours, place the solution in a drying oven at 80°C, keep it warm for 24 hours, and collect the composite phase change material of the physical mixture of nanoparticles and LDH.
[0049] test
[0050] The endothermic and exothermic properties of the LDH-based composite phase change material with light-to-heat conversion performance prepared in Example 1 were tested using a DSC tester. The DSC curve is as follows: Figure 2 As shown. Figure 2 It can be seen that the DSC melting curve and solidification curve of the composite phase change material have not changed significantly compared with paraffin, indicating that the prepared LDH-based carrier material has almost no effect on the phase change process of the phase change material. At the same time, the melting enthalpy of the prepared LDH-based composite phase change material is 131 J / g, and the solidification enthalpy is 138 J / g, indicating that the prepared LDH-based composite phase change material has excellent phase change energy storage capacity.
[0051] The photothermal conversion performance of the composite phase change materials prepared in Example 1 and Comparative Example 1 was tested by xenon lamp irradiation. The photothermal conversion curves are shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the light-to-heat conversion capability of the LDH-based composite phase-change material with uniformly distributed nanoparticles prepared in the present application is significantly better than that of the composite phase-change material with directly added magnetic nanoparticles.
[0052] The above-mentioned specific embodiments of the present application are merely preferred embodiments for explaining the present application, and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications without creative contribution as needed. However, any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing an LDH-based composite phase change material with light-to-heat conversion performance, characterized in that: The following steps are involved: Step 1, using ZIF-67 as a template, chemically etching it with a metal salt to obtain LDH with uniform distribution of different metal elements; the metal salt includes one or more of iron salt, molybdenum salt and nickel salt, and the LDH with uniform distribution of different metal elements includes one or more of Mo-Co LDH, Ni-Co LDH and Fe-Co LDH; Step 2: calcining in a reducing atmosphere to reduce the metal elements in the LDH with uniform metal element distribution to metal nanoparticles in situ, thereby obtaining a phase change carrier with uniformly dispersed metal nanoparticles; Step 3: Vacuum the phase change carrier prepared in step 2 at 80°C~120°C for 4 hours, then place it in a solution containing a phase change core material, heat it to 25~100°C, stir it for 1~24 hours, and then place it in a 50~120°C oven to dry for 2~24 hours; the phase change core material includes a mixture of polyols, fatty acids and hydrocarbons.
2. The method for preparing the LDH-based composite phase change material with light-to-heat conversion performance according to claim 1, characterized in that: The specific method of step 1 is: Step 1.1: Using Co(NO3)2 and 2-methylimidazole as precursors, dodecahedral ZIF-67 was synthesized by standing in methanol at room temperature for 12 to 24 hours; Step 1.2: Dissolve ZIF-67 in ethanol solution and metal salt in deionized water, and ultrasonicate for 5-15 minutes respectively; Step 1.3: The two solutions in step 1.2 are then mixed and reacted at 60-80°C for 15 min~24 to obtain LDH with uniform distribution of different metal elements.
3. The method for preparing the LDH-based composite phase change material with light-to-heat conversion performance according to claim 1, characterized in that: The specific method of step 2 is: placing the LDH with uniform distribution of different metal elements obtained in step 1 in a crucible, heating it at 300-450°C for 2-3 hours at a heating rate of 1-2°C / min under a reducing atmosphere, and cooling it to room temperature to obtain a phase change carrier with uniformly dispersed metal nanoparticles.
4. The method for preparing the LDH-based composite phase change material with light-to-heat conversion performance according to claim 3, characterized in that: The reducing atmosphere is a mixed atmosphere of 5% hydrogen and 95% argon.
5. The method for preparing the LDH-based composite phase change material with light-to-heat conversion performance according to claim 1, characterized in that: The polyol includes one or more of polyethylene glycol 1000-20000, pentaerythritol, and neopentyl glycol; the fatty acid includes one or more of stearic acid, myristic acid, palmitic acid, capric acid, lauric acid, pentadecanoic acid, and sebacic acid; and the hydrocarbon mixture is paraffin.
6. The method for preparing the LDH-based composite phase change material with light-to-heat conversion performance according to claim 1, characterized in that: The solution containing the phase change core material is an aqueous solution, an alcohol solution or a n-hexane solution; the concentration of the phase change core material solution is 10-15 g / L, and the loading amount of the composite phase change material is 50-80%.
7. An LDH-based composite phase change material with light-to-heat conversion performance, characterized in that: The method is prepared by any one of claims 1 to 6.
Citation Information
Patent Citations
Magnetic thermal-photothermal double-drive energy conversion and storage polymer nano composite phase-change energy-storage material and preparation method thereof
CN106010458A
Phase-change composite material with photo-thermal conversion function and preparation method thereof
CN110257019A
Metal organic framework derived carbon-based photo-thermal phase change energy storage material as well as preparation method and application thereof
CN114410279A
Energy storage wood with layered double hydroxide and polypyrrole as photo-thermal super-hydrophobic surface and preparation method
CN114619531A
Bimetal MOF (Metal Organic Framework) derived graphitized carbon-based photo-thermal composite phase change material as well as preparation method and application thereof
CN114774085A